A clinicopathologic study of 1,047 cases of salivary gland tumors in Thailand - Rachai Juengsomjit (2018)
© Quintessenz. All right reserved. Objective: The objective of this study was to analyze the clinicopathologic data of salivary gland tumors in Bangkok, Thailand. Method and Materials: Cases diagnosed with salivary gland tumors were retrieved from a dental school and a medical school in Bangkok, Thailand. Clinicopathologic data were recorded and analyzed with respect to gender, age, site, and histologic type. Results: Of the 411,851 cases, 1,047 salivary gland tumors (0.2%) were found. The male to female ratio was 1:1.2. The age of patients ranged from 1 to 88 years with an average age of 47.1 years. 721 cases were benign tumors (68.8%) while 326 cases (31.2%) were malignant tumors. The parotid gland was the most common site (62.7%), followed by the submandibular gland (18.8%), and the intraoral minor salivary glands (18.0%). Among the intraoral minor salivary glands, palate was the most common site (49.2%). The most common benign and malignant tumors were pleomorphic adenoma and mucoepidermoid carcinoma. Conclusions: Salivary gland tumors are rare. Compared with Western countries, the prevalence of polymorphous low-grade adenocarcinoma (PLGA) in Southeast Asia is low. Data from this study may be helpful for dentists in making differential diagnoses.